FUNGSI ALAT MUSIK SULIM DALAM PESTA PERKAWINAN ADAT MASYARAKAT BATAK TOBA - Eva Florida Simanjuntak (SURYA SENI, 2008)
Sulim is bambo ﬂ ute of Batak Toba society, is one of many traditional music instrument of Batak Toba society. It must combine ceremony. This instruments be close to the Batak Toba people since Opera Batak ceremony by Tilhang OberlinGultom. After that, Batak Toba people always use the sulim on some of the traditional ceremony.There are three questions that need explanation thy are: (1) How is the chronology of traditional wedding ceremony of Batak society, (2) What is the function of sulim in the traditional mariage ceremony of Batak Toba society, and (3) Whythe Batak Toba people use the sulim in their traditional mariage, in this problem to be explain by multi diciplined approach. Resuld of this reseach aprove that traditional mariage ceremony performed closely by the people. Music ansambel with the sulim instruments after to accompanyitems of ceremony. Sulim as the main choise to accompany the ceremony because it has the register of note that longer than another instruments, for example hasapi, sarune etek, sarune bolon, and garantung; sulim has speciﬁc expression and style.Keyword: Sulim